Pharmacological modulation of KATP channels. (April 2002) - Gribble, F. M.; Reimann, F.
Abstract : Pharmacological modulation of ATP-sensitive K + (KATP ) channels is used in the treatment of a number of clinical conditions, including type 2 diabetes and angina. The sulphonylureas and related drugs, which are used to treat type 2 diabetes, stimulate insulin secretion by closing KATP channels in pancreatic β-cells. Agents used to treat angina, by contrast, act by opening KATP channels in vascular smooth and cardiac muscle. Both the therapeutic KATP channel inhibitors and the KATP channel openers target the sulphonylurea receptor (SUR) subunit of the KATP channel, which exists in several isoforms expressed in different tissues (SUR1 in pancreatic β-cells, SUR2A in cardiac muscle and SUR2B in vascular smooth muscle). The tissue-specific action of drugs that target the KATP channel is attributed to the properties of these different SUR subtypes. In this review, we discuss the molecular basis of tissue-specific drug action, and its implications for clinical practice.